2000
DOI: 10.1207/s15324834basp2203_2
|View full text |Cite
|
Sign up to set email alerts
|

Bolstering and Undercutting Use of the Elderly Stereotype Through Communication of Exemplars: The Role of Speaker Age and Exemplar Stereotypicality

Abstract: This study explores how older speakers' descriptions of other older persons might attenuate or bolster the use of the elderly stereotype by young listeners. Older women's descriptions were expected to have more impact on young participants, presumably because older persons are considered experts about elderly persons and the elderly persons seem unlikely to have a hidden agenda in describing other elderly persons. Using a 2-experiment ploy, young adult women initially listened to an audiotape of an older woman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Previous research has shown that the assumptions people make about a group can be challenged by presentation of counter-stereotypic members of that group (e.g., Dasgupta & Asgari, 2004; Dasgupta & Greenwald, 2001; Duval et al, 2000; Plant et al, 2009). Counter-stereotype interventions in aging to date have focused on likability and general stereotypes as targets (Dasgupta & Greenwald, 2001; Duval et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that the assumptions people make about a group can be challenged by presentation of counter-stereotypic members of that group (e.g., Dasgupta & Asgari, 2004; Dasgupta & Greenwald, 2001; Duval et al, 2000; Plant et al, 2009). Counter-stereotype interventions in aging to date have focused on likability and general stereotypes as targets (Dasgupta & Greenwald, 2001; Duval et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the assumptions people make about a group can be challenged by presentation of counter-stereotypic members of that group (e.g., Dasgupta & Asgari, 2004; Dasgupta & Greenwald, 2001; Duval et al, 2000; Plant et al, 2009). Counter-stereotype interventions in aging to date have focused on likability and general stereotypes as targets (Dasgupta & Greenwald, 2001; Duval et al, 2000). The present research instead focuses on social status to suggest that both cultural exposure to older adults in prestigious positions and manipulated exposure in an experimental setting predicts a smaller discrepancy between how participants view middle-aged adults compared with older adults’ social status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These attitudes, and the stereotypes they engender, ''are not developed or expressed in a social vacuum,'' but rather, tend to be communicated to others (Ruscher, 2001, p. 44). The communication of prejudice is especially harmful because prejudiced attitudes obtained second-hand tend to be stronger than their original sources (Duval, Ruscher, Welsh, & Cantanese, 2000), and those who express stereotypes are more likely to think stereotypically about their targets in the future (Ruscher & Duval, 1998). Thus, as Greenberg and Pyszczynski (1985) so well put it, when these attitudes are communicated, they ''spread like a social disease,'' and magnify the resultant harm.…”
Section: Introductionmentioning
confidence: 99%